2005
DOI: 10.1007/s00018-004-4297-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of insulin and IGF-1 signaling in longevity

Abstract: There are many theories of aging and parameters that influence lifespan, including genetic instability, telomerase activity and oxidative stress. The role of caloric restriction, metabolism and insulin and insulin-like growth factor-1 signaling in the process of aging is especially well conserved throughout evolution. These latter factors interact with each other, the former factors and histone deacetylases of the SIR family in a complex interaction to influence lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 320 publications
(262 reference statements)
2
115
0
9
Order By: Relevance
“…60 Presumably, this can be ascribed to accelerated autophagy. 11,61 Calorie restriction also prolongs life and this, too, has been ascribed to increased autophagy.…”
Section: Defective Insulin Signaling Autophagy and Lifespanmentioning
confidence: 99%
“…60 Presumably, this can be ascribed to accelerated autophagy. 11,61 Calorie restriction also prolongs life and this, too, has been ascribed to increased autophagy.…”
Section: Defective Insulin Signaling Autophagy and Lifespanmentioning
confidence: 99%
“…Přitom v živočišné říši se jedná o naprosto fyziologický jev, typický pro období růstů, dospívání i pro těhotné ženy. Podobné nálezy se týkají nejen subkmene obratlovců, ale dokonce i jiných živočišných kmenů (42,89). Inzulinovou rezistenci lze i interpretovat jako selektivní odpověď, jak tkáně či orgány reagují na inzulin.…”
Section: Inzulinová Rezistence U Kriticky Nemocnýchunclassified
“…Reduced activity of the insulin/IGF1 pathway was sufficient but not strictly required to extend lifespan in a variety of organisms including worms, flies and mice. 51 Animal experiments indicated that the inverse relationship existing between these two pathways (inhibition of PI3K/ Akt and activation of AMPK) represents an essential intracellular switch for transducing the inhibitory effect of dietary energy restriction on mammary carcinogenesis. 52 Among the several or contributing to the onset of diseases have not been reported to date in FoxO3A locus, except for a chromosomal translocation, t(6; 11), found in a few cases of acute myeloid leukemia, which involves a fusion between MLL and FoxO3A.…”
Section: The Ampk-foxo Axis: Balancing Nutrient Sensing and Healthspamentioning
confidence: 99%